Identification of Peptides from a Phage Display Library for Differentiating Newcastle Disease Virus Pathotypes - Lee, Tong Chuan (2006)
Newcastle disease virus (NDV) strains can be classified as virulent or avirulent based upon the severity of the disease.Biopanning experiments were performed using a disulfide constrained phage display heptapeptide library against three pathotypes of NDV strains: velogenic (highly virulent), mesogenic (moderately virulent) and lentogenic (avirulent).A phage clone bearing the peptide sequence SWGEYDM was isolated and shown to be able to differentiate virulent from avirulent NDV strains.This phage clone was employed as a capturing reagent in a dot-blot assay to detect virulent NDV strains in allantoic fluid of embryonated chicken eggs. The performance of the dot blot assay was compared with that of mean death time (MDT) in embryonated chicken eggs and the reverse transcription-polymerase chain reaction (RT-PCR) methods.The dot blot was shown to be specific for virulent NDV strains and able to differentiate between the virulent and avirulent NDV strains